Comparison of Logistic Euroscore with Euroscore II in predicting postoperative mortality in adult cardiac surgical patients - Parajuli, Santosh Sharma; Rajbhandari, Nivesh; Thakur, Apurb (Nepalese Heart Journal, 2022)
Background: Logistic Euroscore and Euroscore II are widely used in predicting perioperative mortality after cardiac surgery; however the data regarding the superiority of one over the other in predicting outcome regarding 30 days mortality in isolated coronary artery surgeries are not consistent. This study assessed the predictive accuracy of logistic Euroscore versus Euroscore II in determining 30 days mortality after isolated CABG surgery in a single cardiac center of Nepal.Methods: One hundred and forty-two patients scheduled for isolated coronary artery bypass surgery during the one-year period was taken for this prospective observational study. The predictive post-operative mortality was calculated using both of the scoring system. The actual mortality observed during the 30 day of postoperative period was recorded and the findings were compared with the predictive post-operative mortality according to the scoring systems by using area under the receiver operating characteristics curve (AUC).Results: One hundred and forty-two patients were enrolled in this study and average cross clamp time was 65.92 +/- 26.39 minutes and total cardiopulmonary bypass time was 102.90 +/- 37.32 minutes. The average hours of ventilator stay was 9.56 +/- 8.45 and total days of ICU stay was 4.96 +/- 2.00. The observed 30 day mortality was 2.11% (95% CI, 1.96-2.36%) which was slightly better predicted by ESL 2.40% (95% CI, 2.04-2.76%) in comparison to ES II 1.44% (95% CI, 1.22-1.66%). The AUC value was 0.917 (0.817-1.000) for ESL and 0.946 (0.887-1.000) for ES II in predicting 30 day postoperative mortality and were comparable.Conclusion: Both of the logistic Euroscore and Euroscore II are comparable to each other in predicting 30 day postoperative mortality after isolated CABG surgery.